ANALYSIS OF STUDENTS MISCONCEPTIONS IN SOLVING QUADRATIC INEQUALITIES: A CASE STUDY IN THE INFORMATICS STUDY PROGRAM - Devita, Dewi; Erdriani, Deby; Marhayati, Laila (Jurnal Manajemen Pendidikan, 2026)
Strong mathematical foundations are crucial for informatics students, yet they frequently encounter difficulties with foundational topics such as quadratic inequalities, revealing a significant disconnect between procedural competence and conceptual understanding. This study investigates the nature and origins of misconceptions in solving quadratic inequalities among informatics students, using Vergnaud’s Theory of Conceptual Fields as an analytical framework. A qualitative case study was conducted with 28 students from an Informatics Study Program. Data were collected through triangulation, including analysis of written solutions to five inequality problems and a self-report questionnaire featuring Likert-scale and open-ended questions. The analysis followed four stages: error identification, frequency profiling, cognitive scheme analysis, and representational analysis. Findings indicate that the most common errors were procedural, notably incorrect sign reversal when multiplying or dividing by a negative number (46.4% reported high difficulty) and misdetermining solution intervals for perfect square inequalities (39.3%). Conceptual errors were linked to underdeveloped cognitive schemes, especially in connecting critical points to interval testing and translating contextual problems into mathematical symbols.